Hubungan Kepemilikan Jamban Dengan Kejadian Diare Di Dusun Katoang, Desa Bontomatinggi Kabupaten Maros: The Relationship Of Laterine Ownership And The Incident Of Diarrhea In Katoang Hamlet, Bontomatinggi Village, Maros District - Puspitasari, Ayu; Suyuti , Sartika; Nurgahayu, Nurgahayu; Abdullah, Nurhikmah (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: Diarrhea is still a major problem in developing countries, including Indonesia Aim: The aim of this research is to determine the relationship between latrine ownership and the incidence of diarrhea in Katoang Hamlet Method: The type of research used is analytical observational with a cross sectional study approach. This research was conducted in Katoang Hamlet, Kab. Maros. The total sample in this study was 71 families using total sampling. The data collection technique was carried out through the interview method using a questionnaire sheet. Results: Based on the results of the Chi-Square analysis test, a significant value (p-value) = 0.003 was obtained, where the p-value was >0.05, meaning there was a significant relationship between latrine ownership and the incidence of diarrhea in Katoang Hamlet, Bontomatinggi Village. Conclusion: It is hoped that the community will increase their ownership of healthy toilets to avoid diarrhea and that the local government will regularly provide education regarding the importance of owning healthy toilets.